2020
DOI: 10.9734/mrji/2020/v30i530221
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hydrocarbon Utilizing Bacteria and Fungi Associated with Crude Oil Contaminated Soil

Abstract: Many substances known to have toxic properties are regularly introduced into the environment through human activity. These substances which include hydrocarbons range in degree of toxicity and danger to human health. Frequent oil spills incidents have become a problem to ecological protection efforts. Conventional methods to remove, reduce or mitigate toxic substances introduced into soil via anthropogenic activities suffer setbacks due to the level of risk involved but bioremediation offers an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The dominant fungal genera found in the Ecopile soil were Ochroconis (∼15%), Pseudallescheria (9%), Gaertneriomyces (9%), and Fusarium (7%), many of which have been reported to be present in contaminated soils. Borowik et al, (2017) showed that hydrocarbon-polluted soil was dominated by fungi from the genera Fusarium (37.9%), Candida (13.8%), Microsporum (13.8%), and Penicillium (13.8%), while Ogbonna et al, (2020) identified a number of hydrocarbon-degrading fungi in oil-contaminated soil including some species of Fusarium, Penicillium, Kodamaea, and Lentinus. Wu et al, (2020a) and Wu et al, (2020b) reported the presence of Ochroconis species in two different petroleumcontaminated soils in China at relative abundances of 1-5%.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant fungal genera found in the Ecopile soil were Ochroconis (∼15%), Pseudallescheria (9%), Gaertneriomyces (9%), and Fusarium (7%), many of which have been reported to be present in contaminated soils. Borowik et al, (2017) showed that hydrocarbon-polluted soil was dominated by fungi from the genera Fusarium (37.9%), Candida (13.8%), Microsporum (13.8%), and Penicillium (13.8%), while Ogbonna et al, (2020) identified a number of hydrocarbon-degrading fungi in oil-contaminated soil including some species of Fusarium, Penicillium, Kodamaea, and Lentinus. Wu et al, (2020a) and Wu et al, (2020b) reported the presence of Ochroconis species in two different petroleumcontaminated soils in China at relative abundances of 1-5%.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the microscopic/macroscopic characteristics revealed the presence of Aspergillus niger, Mucorsp, Aspergillus flavus, Fusarium sp, Aspergillus japonicas, Rhizopus nigricans, Trichoderma sp, Penicillum sp. The frequency of occurrence of fungal isolates showed that a total of twentythree (23) fungal isolates were gotten from the samplesthe frequency of occurrence of the isolatesis higher than four (4) isolates reported by Ogbonna et al, (2020).The possible reason could be as a result of the duration of simulation, in this case 21 days simulation was allowed in order to mimic a naturally polluted soil ( (Varjani and Gnansounou, 2017) Aspergillus sp and Fusarium sp were the most frequent occurring isolates identified during the course of this study. This is followed by Penicillium sp, Mucor sp with Rhizopus sp and Trichoderma sp being the least as shown Table 3.…”
Section: Resultsmentioning
confidence: 78%
“…SD-43 from steel industry waste posing inbuilt mechanisms for adapting to their environment. It was noted that this organism plays a vital role in remediation and clean-up of oil spillage by utilizing crude oil as its sole carbon source, low cost and environmentally friendly (Guerra et al, 2018) and spore former shielding them from the noxious effects of the hydrocarbon (Ogbonna et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations